(3CMGOjK Yf LeGYI ef GdTjhNs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj,J (B833 (3g` s
(3ChdgG (B:s
(3GNHQfG GdTjN GdGeGe GdYGde GdaGVd Yde GdOjf CHh GdMSf Ydi Hf eMeO Hf YHO GdUeO GdSNGhi bQCg Ydjg hCfG GSeY ai TgQ QeVGf s
(3BNQgG (B:s
(3abGd ef Gjf GfJ bdJ ef Cgd GdHUQI bGd ef GdeOjfI GdPjf jMHhf YKeGf Hf YaGf abGd CNQL Yfi aEfg YKeGfi NHjK s
(3GdfSNI HgG MhGTs
(3YdjgG SeGYGJ egeIs
(3HBNQg eYGQVI Ydi GdCUd GdPi UhQ efgs
(3JHUQI GdYfhGf (B:s
(3QhGjI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs